Cardiorespiratory fitness in patients with Chronic Obstructive Pulmonary Disease - Correia, Ana Rita (2019)
2nd International Congress of CiiEM - Translational Research and Innovation in Human and Health Science. 11-13 June, 2017, Campus Egas Moniz, Monte de Caparica, Portugal